2009
DOI: 10.1103/physrevlett.102.040403
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Quantum Phase Estimation

Abstract: By using a systematic optimization approach we determine quantum states of light with definite photon number leading to the best possible precision in optical two mode interferometry. Our treatment takes into account the experimentally relevant situation of photon losses. Our results thus reveal the benchmark for precision in optical interferometry. Although this boundary is generally worse than the Heisenberg limit, we show that the obtained precision beats the standard quantum limit thus leading to a signifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
499
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(521 citation statements)
references
References 23 publications
8
499
0
Order By: Relevance
“…A post-selected proof of principle experiment that employs some of these optimal states was recently performed [66]. Note that, for very low values of loss, NOON states retain their optimality [104,106], and can be approximated by states that are easy to generate [67,68]. Also, a very simple proposal based on parametric downconversion which can be realized without post-selection was proposed in [72]: it can achieve the Heisenberg bound for low loss and degrades gracefully with noise.…”
Section: Quantum Metrology With Noisementioning
confidence: 99%
See 1 more Smart Citation
“…A post-selected proof of principle experiment that employs some of these optimal states was recently performed [66]. Note that, for very low values of loss, NOON states retain their optimality [104,106], and can be approximated by states that are easy to generate [67,68]. Also, a very simple proposal based on parametric downconversion which can be realized without post-selection was proposed in [72]: it can achieve the Heisenberg bound for low loss and degrades gracefully with noise.…”
Section: Quantum Metrology With Noisementioning
confidence: 99%
“…While this means that quantum approaches are useful in highly controlled environments [102] (such as for gravitational wave detection [1]), they only allow for very small enhancements in free-space target acquisition [102]. Nonetheless, the shot noise can be beaten [103] and the optimal states to do so in the presence of loss have been calculated numerically using various optimization techniques for fixed number of input photons [104,105] and for photon-number detection [106]. A post-selected proof of principle experiment that employs some of these optimal states was recently performed [66].…”
Section: Quantum Metrology With Noisementioning
confidence: 99%
“…On the other hand , however, interaction between a system and an environment is unavoidable in reality, and the quantum decoherence induced by such interactions may decrease the QFI and destroy the quantum entanglement in the probe system exploited to improve the precision. In this regard, It has been shown that the interaction between a system and an environment usually makes the measurements noisy, which in turn degrades the estimation precision [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Current research on linear interferometers is directed at the search for optimal input states and output measurements [2][3][4][5][6][7][8][9][10][11][12], adaptive phase measurement schemes [13][14][15][16], and the influence of particle losses [17][18][19]. Several proof-ofprinciple experiments reaching a sub shot-noise sensitivity have been performed, for a fixed number of particles with photons [20][21][22][23][24] and ions [25], while squeezed states for interferometry with a non-fixed number of particles have been prepared with Bose-Einstein-condensates [26][27][28][29][30], atoms at room temperature [31] and light [32,33].…”
Section: Introductionmentioning
confidence: 99%